ENTREPRENEURIAL START-UP PROCESS: THE ROLE OF SOCIAL CAPITAL AND SOCIAL ECONOMIC CONDITION - Enkhbold Chuluunbaatar,; Ottavia,; Ding-Bang Luh,; Shiann-Far Kung, (Asian Academy of Management Journal, 2011)
Entrepreneurship is a complex phenomenon which involves not only economic activity, but also social mechanisms. The intention to become entrepreneur is not only a matter of one’s individual personality, but also his/her interaction with the social environment. This study has two main objectives. First, predicting the existence of entrepreneurial behavioral intention in different social economic conditions; examining how entrepreneurial behavioral intention formulates entrepreneurial behavior; and finally identifying how social capital influences the relationship. Second, it aims to reveal the differences between entrepreneurs in a relatively mature free market economy (Taiwan) and a newly emerging free market economy (Mongolia). The analysis shows that social economic conditions affect the formation of entrepreneurial intention. There are different approaches of building social capital in a relatively mature market and its newly emerging counterpart. The tendency of high trust and social ties were found in Taiwanese entrepreneurs, while monitoring is commonly found among Mongolian entrepreneurs.